The determination of the endogenous market penetration and compliance rate of advanced traveler information systems - Li, Shu G. (Transport, 2004)
We consider a specific ATIS which objective is to reduce drivers’ travel cost uncertainty with recurrent network congestion through the provision of traffic information. Most of the studies premise of the use of a static model for an essentially dynamic problem. We propose a multi‐user stochastic dynamic route and departure time model for modeling interactions among travelers. We propose a nested‐logit model for the determination of the market penetration and compliance rate of ATIS. The upper level is for market penetration; the lower level is for compliance rate. Then an iterative algorithm is proposed for the determination of the endogenous market penetration and compliance rate of ATIS and the equilibrium network flow pattern. Finally, the model and algorithm are tested in a simple network.First Published Online: 27 Oct 2010